2013
DOI: 10.1111/j.1752-0606.2012.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Adoptees’ Experiences Balancing Relationships With Biological and Adoptive Mothers Post‐Reunification

Abstract: Using a feminist postmodern perspective and the sensitizing concept of split loyalties from Contextual Theory, the primary purpose of this qualitative study was to develop a better understanding of how adult female adoptees from closed adoptions negotiate relationships with their adoptive and biological mothers post-reunion. We conducted semi-structured individual interviews with nine adult female adoptees, ages 28-52, who were adopted prior to the age of two. Six were Caucasian, three were African American, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…An extended review of the English language literature between the years 2000 to 2016 revealed a paucity of material specifically relating to adoptees as parents. Only two peer reviewed studies were funded that focused on adopted woman as mothers (Conrick and Brown, 2010; Phillips, 2009), although others concerned with investigating other aspects of the adoption experience made some reference to the parenting life stage (Moyer and Juang, 2011; Richardson, Davey and Swint, 2013; Rosnati, Greco and Ferrari, 2015; Rushton, et al., 2013), as did several reports within the grey literature 2 (Kenny, et al., 2012; Masso and Whitfield, 2003; Senate Community Affairs Reference Committee, 2012). Two seminal practice guides outside of the designated time period have also been included (Brodzinsky, Schechter and Marantz Henig, 1992; Reitz and Watson, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…An extended review of the English language literature between the years 2000 to 2016 revealed a paucity of material specifically relating to adoptees as parents. Only two peer reviewed studies were funded that focused on adopted woman as mothers (Conrick and Brown, 2010; Phillips, 2009), although others concerned with investigating other aspects of the adoption experience made some reference to the parenting life stage (Moyer and Juang, 2011; Richardson, Davey and Swint, 2013; Rosnati, Greco and Ferrari, 2015; Rushton, et al., 2013), as did several reports within the grey literature 2 (Kenny, et al., 2012; Masso and Whitfield, 2003; Senate Community Affairs Reference Committee, 2012). Two seminal practice guides outside of the designated time period have also been included (Brodzinsky, Schechter and Marantz Henig, 1992; Reitz and Watson, 1992).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, despite this diversity, there were a number of shared themes. These included: pregnancy and birth may precipitate a sense of loss and grief (Brodzinsky, Schechter and Marantz Henig, 1992; Conrick and Brown, 2010; Masso and Whitfield, 2003; Phillips, 2009; Pinkerton, 2010) and depression and anxiety (Kenny, et al., 2012; Masso and Whitfield, 2003); wanting to give children the best possible childhoods (Moyer and Juang, 2011); having children may prompt the adoptee to revaluate their relationships with their adoptive parents (Brodzinsky, Schechter and Marantz Henig, 1992; Conrick and Brown, 2010; Kenny, et al., 2012; Masso and Whitfield, 2003; Richardson, Davey and Swint, 2013; Reitz and Watson, 1992; Senate Community Affairs Reference Committee, 2012); becoming a mother was important to the adopted woman’s decision to ‘search’ and/or have contact with birth family (Conrick and Brown, 2010; Pinkerton, 2010; Richardson, Davey and Swint, 2013); parenthood often leads to a review of adoption status in which partners can play a significant supportive role (Rosnati, Greco and Ferrari, 2015; Rushton, et al., 2013); mothering children is a time for exploration and review of personal identity (Grotevant, et al., 2007), which may bring an opportunity for an expanded integration of one’s sense of self (Penny, Borders and Portnoy, 2007). …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Including a dedicated theory section. One practice that seemed particularly helpful in incorporating theories in the research input was including a section titled "theoretical framework" or a similar name, which promptly orients readers to the study's connections to existing theories (e.g., Hardy, Soloski, Ratcliffe, Anderson, & Willoughby, 2015;Inman, Altman, Kaduvettoor-Davidson, Carr, & Walker, 2011;Richardson, Davey, & Swint, 2013). Similarly, some papers featured a section titled "theoretical emphasis and background" (e.g., Bay, Blow, & Yan, 2012) or "theoretical foundation" (e.g., Gambrel & Piercy, 2015).…”
Section: Practical Suggestions For Effective Theory Incorporationmentioning
confidence: 99%
“…Also, a good illustrative mix of quantitative methods can be seen in the work of Cornett and Bratton (); Christenson, Crane, Bell, Beer, and Hillin (); Guo and Slesnick (); and Oka, Sandberg, Bradford, and Brown (). Likewise, good qualitative research can be both sophisticated and important, as illustrated in the work of Gerlock, Grimesey, and Sayre () and Richardson, Davey, and Swint ().…”
mentioning
confidence: 99%